Karakteristik Tingkat Kesukaan Yogurt Bunga Telang (Clitoria ternatea L.) Dengan Penambahan Madu Sebagai Pemanis Alami - Miftahul Jannah; Suciati Zelika; Gustika Alwadania Utami; Jesi Yolani; Ummi Hiras Habisukan (Universitas Nusantara PGRI Kediri, 2023)
This study aims to determine the percentage of butterfly pea flower extract that can produce quality yogurt. In making this yogurt, variations in the extract concentration of 5% and 10% of the butterfly pea flower with a fermentation time of 18 hours, in addition to variations in the addition of honey to the 10% extract and 30 grams of sugar to the 5% extract, and yogurt without giving the butterfly pea extract. The main ingredient used is UHT milk with 200 ml each. Organoleptic testing was carried out to make yogurt in order to find out the level of consumer preference for the exact composition of the butterfly pea flower extract. Samples YBT1 (control), (YBT2 (preferred), YTBT (disliked).